Application for online conferences and meetings. Issue 2 (18th November 2020) - Rifai, Mochammad; Fitrianah, Devi
Abstract : Purpose: This study aims to support an institution to hold an online meeting or conference in the middle of social distancing, which is currently in effect. Design/methodology/approach: In developing this application, rapid application design methodology is used. The implementation used HTML5 and PHP for the Web and MySQL for the database and Agora Software Development Kit. To evaluate the application, the authors had a black box testing method. Findings: This application will support the participant registration process, validation, payment, providing a link to the workshop to the participant, token and room name to be able to join an online meeting or conference up to the process of giving a digital attendance certificate to participants or members participating in it. Originality/value: An integrated Web application provides full services, starting from the registration process, payment, the conference meeting itself and certificate of attendance.